Depression with Somatic Symptoms in Patients Attending Psychiatry OPD of Nepalgunj Medical College - Belbase, Mohan; Adhikari, J.; Khan, T.A.; Jalan, R.K. (Journal of Nepalgunj Medical College, 2016)
Background: Depression is the most common mental health problem but its presentation may not be the same all the time. Presentation of depression in the form of somatic symptoms makes it difficult to identify by untrained eyes which needs detailed investigations before labeling them as having a psychiatric problems.  Methods: This is a descriptive study done in patients attending psychiatry OPD of Nepalgunj Medical College, Kohalpur, for six months from the month of May to October 2014. Results: Out of the 240 study subjects, the most common age group is 21-30 years, 90(37.5%), followed by 11-20 years, 50(20.83%). Among the physical symptoms, Generalized weakness 145(29.84%), loss of appetite 106(21.81%), vague pain (joint/abdomen) 84(17.28%), headache 80(16.46%), burning and tingling sensation 71(14.61%).Conclusions: Depression is a common psychiatric entity but may present in the form of physical symptoms. The commonest being generalized weakness 145(29.84%), followed by loss of appetite 106(21.81%).JNGMC Vol. 12 No. 2 December 2014, Page: 17-19